Pathways between types of crime and criminal social identity: A network approach. (January 2021) - Boduszek, Daniel; Debowska, Agata; Sharratt, Kathryn; McDermott, Danielle; Sherretts, Nicole; Willmott, Dominic; Popiolek, Katarzyna; Hyland, Philip
Abstract: Criminal social identity (CSI) is a factor for criminal behavior. CSI should therefore be a target of interventive strategies aiming to reduce the risk of re-offending. To date, there is limited knowledge on how CSI is expressed among individuals with different criminal histories, undermining the efforts to develop and target appropriate rehabilitative strategies. In the present investigation, network analysis was applied to model the pattern of relationships between different crime types and CSI. In total, eight networks were estimated among prisoners from the USA ( n  = 772), UK ( n  = 638), and Poland ( n  = 1591). Results show different pathways between CSI scores and crime types across samples. CSI formed positive links with acquisitive crime among U.S. and Polish male prisoners. Homicide formed negative associations with CSI among male prisoners from the USA and Poland as well as U.S. female prisoners. Crimes for which an individual is likely to face social stigmatization were positively associated with CSI in U.S. females and UK males. It is anticipated that from these results, we will be able to build a better understanding of the structural relationships between different types of criminal activity and CSI, subsequently leading to more effective rehabilitation strategies. Highlights: Network analysis was applied to model the pattern of relationships between different crime types and CSI. Eight networks were estimated among prisoners from the US ( n  = 772), UK ( n  = 638), and Poland ( n  = 1591). Results show different pathways between CSI scores and crime types across samples. The findings can be used to target rehabilitative programs addressing criminal identity as a risk factor for re-offending.